EMPOWERMENT OF EARTHQUAKE DISASTER VICTIMS IN CUGENANG DISTRICT, CIANJUR REGENCY - Muhamad Farhan Ilyasa (Journal of Economic Empowerment Strategy (JEES), 2025)
Indonesia, located in the Ring of Fire , is highly vulnerable to various types of natural disasters, particularly earthquakes. At the end of 2022, a 5.6 magnitude earthquake struck Cianjur Regency, West Java Province. One of the most severely affected areas was Cugenang District. This disaster caused extensive infrastructure damage, destroying homes, public facilities, and educational facilities. In addition to physical losses, the disaster also had a significant impact on the social, psychological, and economic aspects of the community. This situation demands integrated and comprehensive interventions so that the community can recover quickly and return to optimal social functions. The Community Empowerment Council (MPM) is present as a party that provides support through economic and social-based empowerment programs for disaster victims. This study uses qualitative methods with a descriptive approach that aims to describe the implementation process of the empowerment program in Cugenang District. The results show that approximately 51 beneficiaries received economic business capital assistance. This program is divided into three main clusters: livestock and fisheries, micro, small, and medium enterprises (MSMEs), and agriculture. With this program, it is hoped that the community will not only be able to meet their basic needs, but also be able to improve their standard of living, achieve economic independence, and rebuild a stronger, more sustainable, and more resilient life in the face of possible future disasters.